Unseen architecture ... or of that we don't want to see (REVISTA NODO, 2021)
This essay is based on a lecture made by the author for the International Seminar “The faces of the architect, the different ways of practice the profession”, organized by the Colombian Association of Architecture Schools, presented at the Colombian National University (Universidad Nacional de Colombia) in Bogotá, between march 19th and the 21st, 2014. The invitation was made to share with the students his direct and indirect experiences, as an architect, with communities economically poor, but rich in many other aspects. The main idea was that the architect can be a builder of the forgotten community. This document is not research, but the consideration about being an architect, has developed academically and professionally by the author while, working in popular and informal settlements.
Keywords: Architecture; Suburb; Popular neighborhood; Community; Popular, social.; Social